Aprendemos a desplazarnos en el espacio usando puntos de referencia - Fernández Valencia, Livia Luz (2019)
The present learning session entitled "We learn to move in space using points of reference" has as a population the children enrolled in the 2019 school year, who are in the first grade of Primary Education; third cycle of the Educational Institution Juan Velasco Alvarado_x000D_ The general objective of the learning session is for students to learn to move in everyday space using and representing reference points._x000D_ It is important to work the displacements in space with the students, because it constitutes one of the fundamental logical-mathematical frameworks, which should serve to structure the future abstract-formal thought. In this sense, the knowledge of this process by teachers who attend groups of children in their first years of school life is imperative, since it will depend on the appropriate selection of teaching strategies and learning activities that promote their development.